Analysis of Risk Factors Related to The Accident of Suspected Ectopic Pregnancy at Rsud Dr. Doris Sylvanus - Tammu, Agnes Petni; Arifin, Syamsul; Adnyana, I Gde Hary Eka (Fakultas Kedokteran Universitas Palangka Raya, 2025)
An interrupted ectopic pregnancy is an ectopic pregnancy that has an abortus rupture of the tubal wall. There are several risk factors for KET, namely age, education, occupation, gestational age, and parity. This study aims to determine the relationship between risk factors for the incidence of interrupted ectopic pregnancy at Dr. Doris Sylvanus Hospital in 2019-2021 in terms of maternal age, education, gestational age and parity. The type of research used was analytical observational, with a case control research approach. The sampling technique for the case group used the simple random sampling method, obtained a sample size of 45 respondents. As for the control group, it was carried out by systematic random sampling with a control number of 45 respondents. Statistical tests used, namely descriptive tests and Chi-Squere tests. The results of this study showed a significant relationship between maternal age and the incidence of KET, there was a significant relationship between maternal education and the incidence of KET, there was no significant relationship between gestational age and the incidence of KET, there was a significant relationship between parity and the incidence of KET. Maternal age, maternal education, and parity are risk factors that have a significant relationship, while gestational age does not have a significant relationship with the incidence of interrupted ectopic pregnancy at Dr. Doris Sylvanus Hospital in 2019-2021